2011
DOI: 10.4314/jopat.v14i1.69409
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis C Virus (HCV) and Human Immunodeficiency Virus (HIV) Co-Infection Among Pregnant Women Attending Antenatal Clinics in Abuja, Nigeria

Abstract: Co-infection with Hepatitis C Virus (HCV) is rare in people living with Human Immunodeficiency

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
3
1
Order By: Relevance
“…In yet another study, Nwokedi and his colleagues [12] reported highest HCV antibody seroprevalence among individuals aged 31-40; followed by the 41-50 age group and found a subsequent steady decline in prevalence with increasing age. The differences between these reports [12,17] and ours may be explained by the onset of hepatitis C related mortality among their populations with resultant lower number of surviving individuals still living with chronic liver disease with increasing age.…”
Section: Author Contributionscontrasting
confidence: 60%
See 1 more Smart Citation
“…In yet another study, Nwokedi and his colleagues [12] reported highest HCV antibody seroprevalence among individuals aged 31-40; followed by the 41-50 age group and found a subsequent steady decline in prevalence with increasing age. The differences between these reports [12,17] and ours may be explained by the onset of hepatitis C related mortality among their populations with resultant lower number of surviving individuals still living with chronic liver disease with increasing age.…”
Section: Author Contributionscontrasting
confidence: 60%
“…This finding is not unexpected considering that hepatitis C is associated with persistent infection with development of chronic liver disease and shows concordance with reports by Azeez-Akande, et al [14] and Karoney, et al [16] of higher HCV antibody seroprevalence in the elderly. In contrast to these findings, Ya'aba, et al [17] found the highest prevalence of hepatitis C among adults aged 26-45 years in 4 health facilities in Abuja, Nigeria. In yet another study, Nwokedi and his colleagues [12] reported highest HCV antibody seroprevalence among individuals aged 31-40; followed by the 41-50 age group and found a subsequent steady decline in prevalence with increasing age.…”
Section: Author Contributionsmentioning
confidence: 82%
“… 27 It is however, higher than coinfection rate of 1.5% in Lagos, 30 0.4% in Abuja. 31 2.4% in Ouagadougou, 32 1.8% in Ethiopia, 33 and 1.65% in Ibadan. 34 On the other hand, the co-infection rate of 6.5% is lower compared to some published rates, including the report of 11.3% in Jos, 35 23.3% in South-west Nigeria, 36 and 33% in Benin City.…”
Section: Discussionmentioning
confidence: 98%
“…Approximately 4-5 million have HCV co-infection while nearly 2-4 million individuals who suffer from HIV are also infected with chronic HBV coinfection [9]. The degree of occurrence varies tremendously from one clime over a period of time [10][11][12][13][14][15]. It is on that premise that observation studies are needed to monitor the level and method of occurrence of these viruses and to execute relevant preventive protocols.…”
Section: Introductionmentioning
confidence: 99%